A high-performance PNN-PZT piezoelectric ceramic material with excellent fatigue resistance, a piezoelectric ceramic element, and a preparation method and application thereof
Patent Information
- Application Number
- CN202611078398.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-16
AI Technical Summary
然而,过高PNN含量会显著削弱材料铁电稳定性,导致居里温度(Tc)大幅下降(通常<180℃),难以满足中高温环境下应用需求;
[0017](1) The PNN-PZT piezoelectric ceramic material provided by this invention has excellent comprehensive performance: its Curie temperature can reach 200-225℃, its piezoelectric coefficient is 350-650 pC/N, and its electromechanical coupling coefficient is 0.50-0.69. The piezoelectric ceramic element prepared from the piezoelectric material has a trigonal-tetragonal phase coexistence characteristic at room temperature, that is, all components are located at the quasi-isomorphic phase boundary (MPB). In addition, the PNN-PZT piezoelectric ceramic material provided by this invention has excellent temperature stability and high-temperature breakdown resistance. Under high temperature conditions, the material can still maintain good inverse piezoelectric characteristics. And no breakdown phenomenon occurs under the simultaneous action of high temperature and high electric field. In particular, the material has excellent positive/inverse piezoelectric fatigue resistance. After multiple electric field cyclic loading, its d 33 and k p With almost no degradation, it exhibits extremely high performance reliability.
Smart Images

Figure CN122916663A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of functional ceramics technology, and relates to a high-performance lead nickel niobate-lead zirconate titanate (Pb(Ni)) with excellent fatigue resistance properties. 1 / 3 Nb 2 / 3 Piezoelectric ceramic materials, piezoelectric ceramic elements, their preparation methods and applications. Background Technology
[0002] Piezoelectric ceramics are key functional materials for converting mechanical energy into electrical energy and are widely used in precision actuation, ultrasonic detection, and intelligent sensing. Among many systems, the PNN-PZT system is considered a core candidate material for next-generation high-performance piezoelectric actuators due to its combination of high dielectric relaxation characteristics of relaxor ferroelectrics and high voltage activity.
[0003] However, the existing PNN-PZT system still faces the following unresolved issues: (1) Curie temperature ( T c ) and piezoelectric properties ( d 33 The trade-off problem: in order to pursue a high voltage coefficient ( d 33 Traditional processes enhance polar nanoregions by increasing the content of the relaxor phase PNN. However, excessively high PNN content significantly weakens the ferroelectric stability of the material, leading to a decrease in the Curie temperature. T c The temperature drops significantly (usually <180℃), making it difficult to meet the application requirements in medium and high temperature environments; (2) Insufficient long-term service stability (fatigue characteristics): PNN-PZT, as a typical "soft" piezoelectric ceramic, has a high piezoelectric coefficient ( d 33 ) and high electromechanical coupling coefficient ( k p However, with high PNN content, the material is highly susceptible to electrical fatigue under alternating electric fields. Its performance is as follows: d 33 and k p The significant degradation severely limits its application in long-life devices; (3) Lack of synergy among multiple performance aspects: As mentioned in problems (1) and (2), existing PNN-PZT systems mostly focus on breakthroughs in a single performance aspect (such as simply pursuing ultra-high performance). d 33 ), lack of understanding of "medium-high Curie temperature" T c - High voltage coefficient ( d 33High electromechanical coupling coefficient k p The four properties of "excellent fatigue characteristics" are synergistically balanced. Summary of the Invention
[0004] To address the aforementioned problems, this invention provides a high-performance PNN-PZT piezoelectric ceramic material with excellent fatigue resistance, a piezoelectric ceramic element, its preparation method, and its applications. The PNN-PZT piezoelectric ceramic material combines high voltage electromechanical / electromechanical coupling performance with excellent fatigue resistance.
[0005] In a first aspect, the present invention provides a high-performance PNN-PZT piezoelectric ceramic material with excellent fatigue resistance, wherein the chemical composition of the PNN-PZT piezoelectric ceramic material is: 0.36Pb(Ni 1 / 3 Nb 2 / 3 The system is 0.23-xPbZrO3-(0.64-x)PbTiO3(0.36PNN-xPZ-(0.64-x)PT), where 0.23≤x≤0.27. In this system, Pb(Ni 1 / 3 Nb 2 / 3 The O3 content is fixed at 0.36, a key parameter determined based on system design and performance optimization. This specific content ensures that the material is in a suitable phase structure coexistence region, thus balancing excellent piezoelectric properties and fatigue resistance. Deviations from this value will disrupt the balance of the PNN-PZ-PT ternary components, leading to phase boundary shifting and performance degradation, making it impossible to guarantee the high performance and fatigue resistance indicators described in this invention.
[0006] Preferably, the Curie temperature of the PNN-PZT piezoelectric ceramic material is 200℃~225℃; The piezoelectric coefficient of the PNN-PZT piezoelectric ceramic material is 350–650 pC / N; The electromechanical coupling coefficient of the PNN-PZT piezoelectric ceramic material is 0.50 to 0.69.
[0007] Secondly, the present invention provides a method for preparing the above-mentioned PNN-PZT piezoelectric ceramic material, comprising the following steps: (1) Using Pb3O4 or PbO, NiO, ZrO2, TiO2 and Nb2O5 as raw materials, weigh the raw materials according to the chemical composition of PNN-PZT piezoelectric ceramic materials and mix them. After pre-firing, ceramic powder is obtained. (2) The obtained ceramic powder is finely ground and pressed into shape to obtain a ceramic blank; (3) The obtained ceramic blank is sintered to obtain the PNN-PZT piezoelectric ceramic material.
[0008] Preferably, in step (1), the mixing method is wet ball milling, and the parameters of wet ball milling include: the mass ratio of raw material powder: ball milling medium: solvent is 1:(3.0~6.5):(0.7~1.5), and the ball milling time is 4~24 hours.
[0009] Preferably, in step (1), the temperature of the pre-firing treatment is 850℃~950℃, the time is 2~4 hours, and the heating rate is 2~5℃ / minute.
[0010] Preferably, in step (2), the fine grinding method is wet ball milling, and the parameters of the wet ball milling include: the mass ratio of ceramic powder: ball milling medium: solvent is 1:(3.0~6.5):(0.7~1.5), and the ball milling time is 4~24 hours.
[0011] Preferably, in step (2), before pressing and molding, the finely ground ceramic powder is mixed with a binder for granulation, and then aged and sieved; the amount of binder added is 4 to 8 wt% of the ceramic powder; the aging time is 18 to 26 hours.
[0012] Preferably, in step (3), the sintering temperature is 1200-1270°C, the time is 2-4 hours, and the heating rate is 2-5°C / minute.
[0013] Preferably, in step (3), before sintering, the ceramic blank is debonded in the air; the debonding temperature is 500-700℃ and the time is 1-5 hours.
[0014] Thirdly, the present invention provides a piezoelectric ceramic element, which is prepared from the above-mentioned PNN-PZT piezoelectric ceramic material.
[0015] Fourthly, the present invention provides a method for preparing the above-mentioned piezoelectric ceramic element, comprising: first preparing silver electrodes on the upper and lower surfaces of the PNN-PZT piezoelectric ceramic material prepared by the above preparation method, and then subjecting it to polarization treatment to obtain the piezoelectric ceramic element; wherein the polarization treatment is polarization for 20 to 40 minutes at an electric field of 25℃ to 60℃ and 3 to 5 kV / mm.
[0016] Fifthly, the present invention provides an application of the above-mentioned piezoelectric ceramic element in piezoelectric actuators, piezoelectric sensors, flexible macroscopic fiber composite material devices, ultrasonic transducers, active vibration control devices, precision positioning devices, and piezoelectric energy harvesting devices. Beneficial effects
[0017] (1) The PNN-PZT piezoelectric ceramic material provided by this invention has excellent comprehensive performance: its Curie temperature can reach 200-225℃, its piezoelectric coefficient is 350-650 pC / N, and its electromechanical coupling coefficient is 0.50-0.69. The piezoelectric ceramic element prepared from the piezoelectric material has a trigonal-tetragonal phase coexistence characteristic at room temperature, that is, all components are located at the quasi-isomorphic phase boundary (MPB). In addition, the PNN-PZT piezoelectric ceramic material provided by this invention has excellent temperature stability and high-temperature breakdown resistance. Under high temperature conditions, the material can still maintain good inverse piezoelectric characteristics. And no breakdown phenomenon occurs under the simultaneous action of high temperature and high electric field. In particular, the material has excellent positive / inverse piezoelectric fatigue resistance. After multiple electric field cyclic loading, its d 33 and k p With almost no degradation, it exhibits extremely high performance reliability. Attached Figure Description
[0018] Figure 1 The X-ray diffraction patterns of the PNN-PZT piezoelectric ceramic materials prepared in Examples 1 (x=0.23), 2 (x=0.24), 3 (x=0.25), 6 (x=0.26), and 7 (x=0.27) of this invention are shown. Figure 2 The average grain size and relative density of the PNN-PZT piezoelectric ceramics prepared in Examples 1 (x=0.23), 2 (x=0.24), 3 (x=0.25), 6 (x=0.26), and 7 (x=0.27) of this invention; Figure 3 The piezoelectric coefficients of the PNN-PZT piezoelectric ceramics prepared in Examples 1 (x=0.23), 2 (x=0.24), 3 (x=0.25), 6 (x=0.26), and 7 (x=0.27) of this invention are... d 33 and electromechanical coupling coefficient ( k p ); Figure 4 This is a comparison diagram of the piezoelectric properties and electromechanical coupling properties of Embodiment 3 of the present invention (x=0.25) before and after undergoing a long-term electrical fatigue test; Figure 5 This is a graph showing the change of unipolar strain in Embodiment 3 of the present invention (x=0.25) during a long-term fatigue cycle. Figure 6 This is a graph showing the change of bipolar strain in Embodiment 3 of the present invention (x=0.25) during the process of temperature increase. Detailed Implementation
[0019] To further illustrate the invention's content, features, and practical effects, the invention will be described in detail below with reference to embodiments. It should be noted that the modification methods of the invention are not limited to these specific implementation methods. Equivalent substitutions and modifications made by those skilled in the art based on their reading of the invention's content, without departing from the spirit and essence of the invention, are also within the scope of protection claimed by this invention.
[0020] This invention provides a PNN-PZT piezoelectric ceramic material without any heterogeneous doping elements, which combines high performance with excellent fatigue resistance. Its chemical composition is: 0.36Pb(Ni) 1 / 3 Nb 2 / 3 The formula is 0.23-xPbZrO3-(0.64-x)PbTiO3(0.36PNN-xPZ-(0.64-x)PT), where 0.23≤x≤0.27. This material system is located in the quasi-isomorphic phase boundary (MPB) region and exhibits trigonal-tetragonal phase coexistence. It can achieve synergistic optimization of high voltage electrical performance and high electromechanical coupling performance under relatively high Curie temperature conditions, and has a long service life.
[0021] In this invention, the material system is precisely positioned within the MPB region by adjusting the relative contents of PZ and PT (0.23 ≤ x ≤ 0.27). If x < 0.23 or x > 0.27, the material will deviate from the MPB region, leading to an imbalance in the trigonal or tetragonal phase content, which in turn causes... d 33 or k pSignificant deterioration occurs. Specifically, as x gradually increases from 0.23 to 0.26, the PZ content in the system increases, while the PT content decreases accordingly. The material gradually shifts from a pre-tetragonal phase structure towards a quasi-isomorphic phase boundary with a better trigonal / tetragonal phase ratio. During this process, the structural anisotropy of the piezoelectric ceramic crystal and the ferroelectric domain structure are further improved. Ferroelectric domains are more likely to undergo reversible flipping under an applied electric field, thus the piezoelectric coefficient, electromechanical coupling coefficient, and unipolar strain of the material show an increasing trend. When x is between 0.25 and 0.26, there is a better phase structure relationship between the trigonal and tetragonal phases, and the material can have both high piezoelectric response and good structural stability, thus exhibiting excellent comprehensive electrical properties and fatigue resistance. When x further increases beyond 0.27, the phase structure of the material shifts towards the trigonal phase enrichment direction, causing the trigonal / tetragonal phase ratio to deviate from the optimal value. At this point, the polarization vector contribution and non-180° domain flipping contribution provided by the tetragonal phase are weakened, thus the piezoelectric performance decreases. If x is less than 0.23, the PT content in the system is relatively high, and the piezoelectric ceramic may exhibit a pre-tetragonal phase characteristic. Excessively high tetragonal phase content enhances crystal anisotropy and raises the polarization reversal energy barrier, which is detrimental to improving piezoelectric response and electrostrain performance. Therefore, both excessively large and excessively small x values may cause the material to deviate from the optimal quasi-isomorphic phase boundary, making it difficult to simultaneously obtain high piezoelectric performance, unipolar strain, and fatigue stability.
[0022] In this invention, the PNN-PZT piezoelectric ceramic possesses high piezoelectric performance, high electromechanical coupling performance, and excellent fatigue resistance primarily due to the phase structure regulation and domain structure response induced by a specific PNN-PZ-PT component ratio, as well as the optimizing effect of this component system on the pre-sintering temperature. Specifically: First, in the 0.36Pb(Ni) of the present invention 1 / 3 Nb 2 / 3 In the 0.64-xPbZrO3-(0.64-x)PbTiO3 system, PNN acts as a relaxor ferroelectric component, which is beneficial for the formation of local disorder and polarization response, giving the piezoelectric ceramic excellent ferroelectric domain response capability. The introduction of this relaxor component can reduce the domain reversal and polarization rotation energy barrier to a certain extent, making the material more prone to polarization reversal and ferroelectric domain reversal under the action of an applied electric field, which is beneficial for improving the piezoelectric coefficient and electromechanical coupling performance. Secondly, by fixing the PNN content to 0.36 and controlling the relative content of PZ and PT within the range of 0.23≤x≤0.27, the ceramic is placed in a suitable quasi-isomorphic phase boundary. At this time, the free energy difference between the two phases is small, and the polarization direction is more likely to rotate or reorient under the action of an external electric field. Therefore, the material can exhibit higher piezoelectric response and electromechanical coupling performance. Furthermore, the specific composition described in this invention can also improve the stability of piezoelectric ceramics under cyclic electric fields. Traditional piezoelectric ceramics are prone to performance degradation during long-term electric field cycling due to defect migration, domain wall pinning, and localized stress concentration. In contrast, the PNN-PZT ceramic described in this invention is located at a quasi-isomorphic phase boundary, and its polarization response does not entirely rely on irreversible domain flipping but includes a significant intrinsic contribution from reversible polarization. This helps reduce the accumulation of irreversible structural damage under cyclic electric fields. Simultaneously, the localized polarization response introduced by the PNN relaxor component can alleviate stress concentration in long-range ferroelectric domains during repeated flipping, making domain structure transformations more stable during electric field cycling, thereby improving the fatigue resistance of the piezoelectric ceramic.
[0023] Therefore, the specific 0.36Pb(Ni) of this invention 1 / 3 Nb 2 / 3 The composition of O3-xPbZrO3-(0.64-x)PbTiO3 is not a simple superposition of components, but rather achieves a balance between high voltage performance, high electromechanical coupling performance and excellent fatigue resistance through the synergistic effect of 0.36PNN relaxor component regulation, PZ / PT ratio optimization and quasi-isomorphic phase boundary.
[0024] This invention further abandons the traditional two-step synthesis process and complex heterogeneous ion doping modification methods, and adopts a one-step solid-state sintering process. By controlling the pre-sintering temperature within the range of 850℃ to 950℃, a stable perovskite phase PNN-PZT solid solution is fully formed between the raw materials. This method does not require additional atmosphere protection, has a simple process flow, and low production cost. At the same time, it can avoid problems such as component segregation, increased defects, performance deterioration, and fatigue resistance degradation that may be caused by complex doping or multi-step heat treatment, thereby achieving a synergistic improvement in piezoelectric properties, electromechanical coupling properties, and fatigue stability.
[0025] In this invention, the PNN-PZT piezoelectric ceramic material does not rely on complex heterogeneous ion doping modification. Instead, it achieves a comprehensive improvement in piezoelectric properties, electromechanical coupling properties, and fatigue resistance through the synergistic effect of a 0.36PNN-xPZ-(0.64-x)PT composition design and pre-firing temperature control. Specifically, this invention, while fixing the PNN content and optimizing the PZ / PT ratio, raises the pre-firing temperature to the range of 850℃ to 950℃. This allows for more complete solid-phase reactions between the various oxide raw materials, promoting the formation of perovskite structures, reducing the tendency for pyrochlore or other impurity phases to form, and improving the phase purity and compositional uniformity of the ceramic powder.
[0026] In the traditional PNN-PZT system, due to Ni 2+ 、Nb 5+ Zr 4+ and Ti 4+Differences in the radius, valence state, and diffusion rate of B-site ions can lead to incomplete solid-state reactions if the pre-firing temperature is too low. This can result in unreacted oxides or the formation of non-perovskite impurities, disrupting the stability of the trigonal / tetragonal coexisting phase structure and reducing the material's polarization response, domain wall mobility, and electromechanical coupling properties. This invention enhances the diffusion and reaction between different components by increasing the pre-firing temperature to 850℃–950℃, allowing PNN, PZ, and PT components to more fully enter the perovskite lattice structure, thus obtaining a uniform and stable PNN-PZT solid solution. This uniform solid solution structure helps maintain suitable quasi-isomorphic phase boundaries, lowers the polarization rotation energy barrier, promotes non-180° domain flips and reversible domain wall motion, and therefore enables the piezoelectric ceramic to exhibit higher piezoelectric coefficients and electromechanical coupling properties.
[0027] Meanwhile, a suitable pre-firing temperature can also improve the sintering activity and subsequent densification behavior of ceramic powders. After pre-firing at 850℃ to 950℃, the powder reaction is more complete and the composition is more uniform, which is conducive to the uniform growth of grains and the formation of a dense ceramic structure during subsequent sintering. Higher density and fewer pore defects can reduce local electric field concentration and stress concentration under the action of an electric field, reduce the risk of crack initiation, defect migration and domain wall pinning during fatigue cycling, thereby improving the structural stability and fatigue resistance of the material under long-term electric field cycling.
[0028] If the pre-sintering temperature is below 850℃, the solid-state reaction between the raw materials may be insufficient, easily leading to uneven composition, residual impurities, or incomplete formation of the perovskite phase, thus deteriorating the piezoelectric response and electromechanical coupling properties of the material. If the pre-sintering temperature is above 950℃, it may cause increased PbO volatilization, local stoichiometry deviation, and increased defect concentration, and may reduce the sintering activity of the powder, leading to abnormal grain growth or uneven microstructure during subsequent sintering, which is detrimental to maintaining piezoelectric properties and fatigue stability. Therefore, this invention controls the pre-sintering temperature within the range of 850℃ to 950℃, achieving a balance between promoting sufficient perovskite phase formation and suppressing lead volatilization and defect increase.
[0029] Therefore, this invention does not improve a single performance by introducing complex doping elements, but rather achieves a synergistic improvement in high voltage electrical performance, high electromechanical coupling performance and excellent fatigue resistance by designing the PNN-PZT matrix composition and coordinating the corresponding pre-sintering temperature window.
[0030] The following is an exemplary description of the preparation process of the high-performance PNN-PZT piezoelectric ceramic material with excellent fatigue resistance provided by the present invention.
[0031] Using Pb3O4 or PbO, NiO, ZrO2, TiO2 and Nb2O5 as raw materials, according to the chemical formula 0.36Pb(Ni 1 / 3 Nb 2 / 3 The raw materials are weighed and mixed into powders: O3-xPbZrO3-(0.64-x)PbTiO3 (0.23≤x≤0.27). For example, wet ball milling is used for mixing, followed by drying. In the wet ball milling method, the raw material powder: milling media: solvent is mixed at a mass ratio of 1:(3.0~6.5):(0.7~1.5) for 4~24 hours, wherein the milling media are zirconium balls, agate balls, or stainless steel balls, and the solvent is anhydrous ethanol or deionized water.
[0032] The mixed powder is pre-fired to obtain ceramic powder. The pre-firing conditions include: in air, at 850℃~950℃, holding for 2~4 hours, with a heating rate of 2~5℃ / min. Within this pre-firing temperature range, the raw materials such as Pb3O4 or PbO, NiO, ZrO2, TiO2, and Nb2O5 in the mixed powder can undergo relatively complete solid-phase reactions, which is beneficial to promoting the formation of the PNN-PZT perovskite phase and improving the uniformity of the phase composition of the ceramic powder. Simultaneously, pre-firing within this temperature range can also reduce the residue of unreacted raw materials, pyrochlore impurities, or other non-perovskite impurities, avoiding their adverse effects on subsequent sintering densification and electrical properties. Furthermore, the ceramic powder pre-fired within this temperature range exhibits good sintering activity, which is beneficial for uniform grain growth and the formation of a dense ceramic structure during subsequent sintering. Higher density and fewer porosity defects can reduce local electric field concentration under an applied electric field, thus improving the piezoelectric properties, electromechanical coupling properties, and fatigue resistance of piezoelectric ceramics. If the pre-firing temperature is too low, the solid-state reaction between raw materials is insufficient, easily leading to residual oxide raw materials, uneven component distribution, or incomplete formation of the perovskite phase. These problems disrupt the stability of the trigonal / tetragonal coexisting structure of PNN-PZT, making it difficult for the material to form uniform and stable quasi-isomorphic phase boundary regions, thereby reducing domain wall mobility and deteriorating piezoelectric and electromechanical coupling properties. Furthermore, unreacted raw materials, impurities, or unevenly composed regions can become inducements for local electric field concentration and defect migration during electric field cycling, further hindering the material's fatigue resistance.
[0033] Ceramic powder is directly pressed into shape (sheets or blocks) to obtain a ceramic body. Preferably, a binder is added to the ceramic powder for granulation, followed by aging, sieving, pressing, and debinding to obtain the ceramic body.
[0034] In an optional embodiment, before pressing and molding, the ceramic powder is finely ground using a wet ball milling method, and then dried to refine the particle size of the ceramic powder. The mass ratio of ceramic powder:milling media:solvent is 1:(3.0–6.5):(0.7–1.5) to obtain a uniform and narrowly distributed particle size. The milling media are zirconium balls, agate balls, or stainless steel balls, and the solvent is anhydrous ethanol or deionized water. The ball milling time is 4–24 hours, and the finely ground powder is then dried to obtain the ceramic powder.
[0035] In an optional embodiment, the binder may be polyvinyl alcohol (PVA) or the like. The amount of binder added may be 4–8 wt.% of the weight of the ceramic powder. The aging time may be 18–26 hours. The sieve mesh size is 40–200 mesh. The conditions for debinding are: maintaining a temperature of 550–700°C in air for 2–4 hours.
[0036] The ceramic blank is placed in a high-temperature furnace and sintered to obtain the piezoelectric ceramic material.
[0037] In an optional embodiment, the sintering conditions include: heating to 1200℃~1270℃ in an air atmosphere at a heating rate not exceeding 5℃ / min, holding at that temperature for 2~4 hours, and then cooling in the furnace. The sintering temperature is crucial to the performance of piezoelectric ceramics. If the sintering temperature is too low, ceramic grain development is restricted, resulting in poor density and the easy formation of pyrochlore impurities. This not only reduces piezoelectric and electromechanical coupling performance but also leads to low subsequent polarization efficiency due to high porosity. If the sintering temperature is too high, it may cause the volatilization of volatile components such as Pb and Ni, abnormal grain growth, and even the formation of a glassy phase, severely damaging the overall performance of the piezoelectric ceramic. Therefore, within the temperature range given in this invention, both high density and effective suppression of component volatilization can be achieved, thereby optimizing the overall performance and ensuring the long-term reliability of the piezoelectric ceramic and related devices.
[0038] The piezoelectric ceramic element provided by this invention is prepared from the piezoelectric ceramic material described above. The method for preparing the piezoelectric ceramic element includes: processing the sintered piezoelectric ceramic to the required size, preparing electrodes, and then subjecting it to polarization treatment to obtain the piezoelectric ceramic element.
[0039] In an optional embodiment, the electrode is prepared by coating both sides of the obtained piezoelectric ceramic material with silver, and then heating it to 600–850°C at a rate not exceeding 3°C, holding it at that temperature for 10–30 minutes to perform silver firing. The polarization treatment parameters include: an electric field strength of 3–5 kV / mm at 25°C–60°C, and a polarization treatment time of 20–40 minutes.
[0040] This invention also provides an application of the aforementioned piezoelectric ceramic element in piezoelectric actuators, piezoelectric sensors, flexible macro-fiber composite devices, ultrasonic transducers, active vibration control devices, precision positioning devices, and piezoelectric energy harvesting devices. Specifically, because the PNN-PZT piezoelectric ceramic material of this invention possesses high piezoelectric performance, high electromechanical coupling performance, and excellent fatigue resistance, it is suitable for piezoelectric functional devices requiring long-term stable electro-mechanical energy conversion. For example, in a piezoelectric actuator, the piezoelectric ceramic material can be used as a driving unit material, achieving large output displacement and driving force at a lower driving voltage through a multi-layer stacked structure, suitable for precision positioning, micro-displacement driving, and optical adjustment. In flexible macro-fiber composite devices, the piezoelectric ceramic material can be cut and arranged before being combined with a flexible substrate, electrode layer, and encapsulation layer to form a piezoelectric actuator or sensor with flexible deformation capability. Due to its excellent electro-strain response and fatigue stability, this material is beneficial for improving the output stability and service reliability of flexible macroscopic fiber composite devices during repeated driving processes. It can be used for active vibration control, deformation regulation, and structural health monitoring in aerospace structures, rail transit equipment, precision mechanical structures, and intelligent composite material structures. In ultrasonic transducers, the piezoelectric ceramic material can serve as a piezoelectric transducer element to achieve the mutual conversion between electrical signals and mechanical vibration or acoustic signals. Its high piezoelectric performance and electromechanical coupling performance are beneficial for improving transduction efficiency and signal response capability, while its excellent fatigue resistance is beneficial for improving the working stability of the transducer under long-term excitation conditions. Therefore, the PNN-PZT piezoelectric ceramic material and its components described in this invention can be widely used in the field of piezoelectric functional devices such as driving, sensing, transduction, vibration control, and energy harvesting.
[0041] The following examples further illustrate the present invention in detail. It should also be understood that the following examples are only for further explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention are within the scope of protection of the present invention. The specific process parameters, etc., in the following examples are merely examples within a suitable range; that is, those skilled in the art can make appropriate selections within the appropriate range based on the description herein, and are not intended to be limited to the specific values in the examples below. Example 1
[0042] In this embodiment 1, 0.36Pb(Ni) 1 / 3 Nb 2 / 3 The preparation process of the piezoelectric ceramic material 0.64-xPbZrO3-(0.23-x)PbTiO3 (x=0.64-x) includes: (1) Weigh the raw material powder Pb3O4 or PbO, NiO, ZrO2, TiO2 and Nb2O5 according to the above chemical formula. Mix them at a mass ratio of raw material: ball: anhydrous ethanol = 1:4.5:1.2 for 6 hours, dry and press into blocks. In an air atmosphere, heat to 850°C at a heating rate of 3°C / min and hold for 2 hours for pre-firing treatment to obtain ceramic powder. (2) Grind the obtained ceramic powder, then finely grind it by wet ball milling for 8 hours and dry it. Then add 7wt% PVA binder of the powder weight, granulate, age for 24 hours, pass through an 80-mesh sieve, press into a circular sheet with a diameter of 13 mm and a thickness of 2 mm, and then heat it to 600℃ in the air to remove the glue for 3 hours to obtain the ceramic body. (3) Place the ceramic blank in the crucible, cover the crucible, and heat it to 1230°C in the air at a heating rate of 3°C / min. Hold it at this temperature for 2 hours and then cool it in the furnace to obtain PNN-PZT piezoelectric ceramic material. (4) The obtained ceramic material is processed into a ceramic sheet with a thickness of 1 mm, cleaned, dried, silvered, dried, heated to 800℃ at a heating rate of 3℃ / min, held for 20 min for silvering, and then polarized for 30 minutes under an electric field of 40℃ and 4 kV / mm to obtain a ceramic element. Example 2
[0043] In Example 2, the preparation process of the PNN-PZT piezoelectric ceramic material is the same as in Example 1, except that the chemical composition of the PNN-PZT piezoelectric ceramic material is 0.36Pb(Ni) 1 / 3 Nb 2 / 3 )O3-xPbZrO3-(0.64-x)PbTiO3(x=0.24). Example 3
[0044] The preparation process of the PNN-PZT piezoelectric ceramic material in Example 3 is the same as in Example 1, except that in step (3), the chemical composition of PNN-PZT is 0.36Pb(Ni) 1 / 3 Nb 2 / 3 )O3-xPbZrO3-(0.64-x)PbTiO3(x=0.25). Example 4
[0045] The preparation process of PNN-PZT piezoelectric ceramic material in this embodiment 4 is the same as that in embodiment 3, except that the sintering temperature in step (3) is 1210℃. Example 5
[0046] The preparation process of PNN-PZT piezoelectric ceramic material in this embodiment 5 is the same as that in embodiment 3, except that the sintering temperature in step (3) is 1250℃. Example 6
[0047] The preparation process of the PNN-PZT piezoelectric ceramic material in Example 6 is the same as in Example 1, except that the chemical composition of PNN-PZT is 0.36Pb(Ni) 1 / 3 Nb 2 / 3 )O3-xPbZrO3-(0.64-x)PbTiO3(x=0.26). Example 7
[0048] The preparation process of the PNN-PZT piezoelectric ceramic material in Example 7 is the same as in Example 1, except that the chemical composition of PNN-PZT is 0.36Pb(Ni) 1 / 3 Nb 2 / 3 )O3-xPbZrO3-(0.64-x)PbTiO3(x=0.27).
[0049] Table 1 lists the performance test data of the PNN-PZT piezoelectric ceramic materials prepared in Examples 1-7.
[0050] Table 1: .
[0051] As shown in Table 1, as x increases from 0.23 to 0.27, i.e., the PZ content in the system gradually increases, the PT content relatively decreases. The piezoelectric coefficient and electromechanical coupling coefficient of the piezoelectric ceramic generally show a trend of first increasing and then decreasing. The above performance changes are mainly related to the phase structure changes caused by the adjustment of the relative PZ / PT content in PNN-PZT. Under the condition of a fixed PNN content of 0.36, when x is low, the PT content in the system is relatively high, and the piezoelectric ceramic exhibits a semi-tetragonal phase characteristic. The semi-tetragonal phase structure usually has strong anisotropy and a high ferroelectric domain flipping energy barrier, which restricts the domain wall movement to a certain extent. Therefore, the piezoelectric coefficient and electromechanical coupling coefficient in Examples 1 and 2 are relatively low. As x gradually increases, the PZ content increases, and the phase structure of the piezoelectric ceramic gradually changes to a quasi-isomorphic phase boundary region where trigonal and tetragonal coexist. At this time, the polarization direction is more likely to rotate or reorient under the action of an applied electric field, and the ferroelectric domain flipping energy barrier is further reduced. Therefore, the piezoelectric coefficient and electromechanical coupling coefficient of the piezoelectric ceramic increase rapidly. When x continues to increase to 0.27, the piezoelectric coefficient and electromechanical coupling coefficient of Example 7 decrease rapidly. This indicates that further increasing the relative content of PZ will cause the system to shift towards a trigonal phase enrichment direction, resulting in a deviation from the optimal phase structure ratio. At this point, the polarization response and strain response of the piezoelectric ceramic decrease rapidly, thus ultimately leading to a rapid decline in piezoelectric performance. Furthermore, as shown in Examples 3 and 4, when the sintering temperature is appropriately increased from 1210℃ to 1230℃, the piezoelectric coefficient and electromechanical coupling coefficient of the piezoelectric ceramic do not show significant attenuation and remain at a high level. This indicates that within a suitable sintering temperature range, appropriately increasing the sintering temperature can promote the densification of the ceramic body, facilitate the elimination of pores, and allow for sufficient grain growth, thereby forming a relatively dense and uniform ceramic microstructure. However, when the sintering temperature continues to increase, both the piezoelectric performance and electromechanical coupling performance of the piezoelectric ceramic decrease. This may be because excessively high sintering temperatures exacerbate the volatilization of substances such as Pb and increase the possibility of defects such as oxygen vacancies forming. These defects can cause domain wall pinning, reducing the ferroelectric domain flipping ability and thus weakening the piezoelectricity and electromechanical coupling properties. In addition, excessively high sintering temperatures may also lead to abnormal grain growth or microstructure inhomogeneity, causing local stress concentration and uneven electric field distribution inside the piezoelectric ceramic, which is detrimental to the realization of piezoelectric properties and fatigue resistance.
[0052] Figure 1The X-ray diffraction patterns of the PNN-PZT piezoelectric ceramic materials prepared in Examples 1 (x=0.23), 2 (x=0.24), 3 (x=0.25), 6 (x=0.26), and 7 (x=0.27) of this invention are shown in the figures. As can be seen from the figures, all components exhibit a pure perovskite structure, and no obvious pyrochlore phase or other impurity phases were detected. This indicates that the one-step solid-state sintering process described in this invention can obtain lead niobate-lead zirconate titanate piezoelectric ceramic materials with high crystallinity and pure phase, effectively avoiding performance degradation caused by impurity phases.
[0053] Figure 2 The figure shows the average grain size and relative density of the PNN-PZT piezoelectric ceramics prepared in Examples 1 (x=0.23), 2 (x=0.24), 3 (x=0.25), 6 (x=0.26), and 7 (x=0.27) of this invention. As can be seen from the figure, the relative density of the material increases monotonically with the increase of component x, and maintains a high relative density overall, indicating that the component range provided by this invention has good sintering compactness. This high density characteristic helps to suppress crack propagation, thereby improving the fatigue resistance of the piezoelectric ceramic. Furthermore, when x is around 0.26, the average grain size of the piezoelectric ceramic material reaches its peak while maintaining a high density. This shows that by controlling different x values, the density and microstructure of the material can be effectively balanced, thereby ensuring the stability and reliability of the piezoelectric performance.
[0054] Figure 3 The piezoelectric coefficients of the PNN-PZT piezoelectric ceramics prepared in Examples 1 (x=0.23), 2 (x=0.24), 3 (x=0.25), 6 (x=0.26), and 7 (x=0.27) of this invention are... d 33 and electromechanical coupling coefficient ( k p As shown in the figure, within the range of 0.23 ≤ x ≤ 0.27, as the component x increases, d 33 and k p All showed a trend of first increasing and then decreasing. At x=0.26, the material exhibited a significant performance peak, among which... d 33 It can reach over 600 pC / N. k p The piezoelectric value can reach 0.68. This indicates that the component range provided by this invention can achieve synergistic optimization of piezoelectric performance and has good tunability, meeting the differentiated requirements of piezoelectric performance in different application scenarios. As x continues to increase (x > 0.26), the piezoelectric performance improves. d 33and k p The piezoelectric ceramic exhibits a decreasing trend because its phase structure gradually shifts from a more favorable trigonal / tetragonal coexistence state to a state enriched in the trigonal phase, causing the ratio of the two phases to deviate from the optimal equilibrium. Simultaneously, the relative content of the tetragonal phase decreases, significantly reducing the polarization vector contribution associated with the tetragonal phase. The domain flipping response capability of the piezoelectric ceramic under an applied electric field decreases significantly, and the contribution of ferroelectric domain flipping weakens. Ultimately, the combined effect of these two factors leads to a significant reduction in piezoelectric performance.
[0055] Using a ferroelectric analyzer, at room temperature, 1 / 2 E C Under 50Hz conditions, piezoelectric ceramics were subjected to electrical fatigue, and after the electrical fatigue was completed, the performance of the corresponding piezoelectric coefficient and electromechanical coupling coefficient was tested.
[0056] Figure 4 This is a comparison of the piezoelectric and electromechanical coupling properties of Example 3 (x=0.25) before and after long-term electrical fatigue testing. As shown in the figure, the PNN-PZT piezoelectric ceramic prepared in Example 3 exhibits improved piezoelectric properties before and after long-term electrical fatigue testing (x=0.25). 6 After high-intensity electrical cycling tests, the piezoelectric coefficient ( d 33 The rate decreased from 567 pC / N before fatigue to 542 pC / N (attenuation Δ). d 33 ≈25 pC / N), electromechanical coupling coefficient ( k p The decay rate decreased from 0.62 before fatigue to 0.61 (Δ decay). k p (≈0.01). The extremely low performance degradation mentioned above indicates that the piezoelectric ceramic described in this invention has excellent resistance to electrical fatigue under long-term cyclic loading, which can ensure the long-term service capability of the device in practical applications.
[0057] Using a ferroelectric analyzer, at room temperature, 1 / 2 E C Under 50Hz conditions, piezoelectric ceramics were subjected to electrical fatigue, and unipolar strain response tests were performed after the corresponding number of fatigue cycles.
[0058] Figure 5 This is a graph showing the change in unipolar strain during long-term fatigue cycling in Embodiment 3 of the present invention (x=0.25). As can be seen from the graph, the unipolar strain of the material remained at approximately 0.15% throughout the entire cycle, with minimal fluctuation. After 10... 6 Strain changes after electrical cycling ΔSThe figure is only about 4.2%. This indicates that the piezoelectric ceramic described in this invention has excellent driving stability and mechanical reliability under long-term cyclic loading, demonstrating its potential to meet the long-life requirements of high-end precision actuators.
[0059] Figure 6 The figure shows the bipolar strain curves of Example 3 (x=0.25) at different temperatures. As can be seen from the figure, the material maintains a significant bipolar electrostriction response throughout the heating process from 40℃ to 160℃, and no electrical breakdown occurs within the test electric field range (3kV / mm). This indicates that the PNN-PZT piezoelectric ceramic described in this invention possesses excellent temperature stability and excellent high-temperature breakdown resistance.
Claims
1. A high-performance PNN-PZT piezoelectric ceramic material with excellent fatigue resistance, characterized in that, The chemical composition of the PNN-PZT piezoelectric ceramic material is: 0.36Pb(Ni 1 / 3 Nb 2 / 3 )O3-xPbZrO3-(0.64-x)PbTiO3, where 0.23≤x≤0.
27.
2. The PNN-PZT piezoelectric ceramic material according to claim 1, characterized in that, The Curie temperature of the PNN-PZT piezoelectric ceramic material is 200℃~225℃; The piezoelectric coefficient of the PNN-PZT piezoelectric ceramic material is 350–650 pC / N; The electromechanical coupling coefficient of the PNN-PZT piezoelectric ceramic material is 0.50 to 0.
69.
3. A method for preparing PNN-PZT piezoelectric ceramic material according to any one of claims 1-2, characterized in that, Includes the following steps: (1) Using Pb3O4 or PbO, NiO, ZrO2, TiO2 and Nb2O5 as raw materials, weigh the raw materials according to the chemical composition of PNN-PZT piezoelectric ceramic materials and mix them. After pre-firing, ceramic powder is obtained. (2) The obtained ceramic powder is finely ground and pressed into shape to obtain a ceramic blank; (3) The obtained ceramic blank is sintered to obtain the PNN-PZT piezoelectric ceramic material.
4. The preparation method according to claim 3, characterized in that, In step (1), the mixing method is wet ball milling. The parameters of wet ball milling include: the mass ratio of raw material powder: ball milling medium: solvent is 1:(3.0~6.5):(0.7~1.5), and the ball milling time is 4~24 hours; Preferably, the pre-firing treatment is performed at a temperature of 850℃ to 950℃ for 2 to 4 hours, with a heating rate of 2 to 5℃ / minute.
5. The preparation method according to claim 3 or 4, characterized in that, In step (2), the fine grinding method is wet ball milling. The parameters of the wet ball milling include: the mass ratio of ceramic powder: ball milling medium: solvent is 1:(3.0~6.5):(0.7~1.5), and the ball milling time is 4~24 hours.
6. The preparation method according to any one of claims 3-5, characterized in that, In step (2), before pressing and molding, the finely ground ceramic powder is mixed with a binder for granulation, and then aged and sieved; the amount of binder added is 4 to 8 wt% of the ceramic powder; the aging time is 18 to 26 hours.
7. The preparation method according to any one of claims 3-6, characterized in that, In step (3), the sintering temperature is 1200-1270℃, the time is 2-4 hours, and the heating rate is 2-5℃ / minute; Before sintering, the ceramic blank is debinded in air; the debinding temperature is 500-700℃ and the time is 1-5 hours.
8. A piezoelectric ceramic element, characterized in that, The piezoelectric ceramic element is made from the PNN-PZT piezoelectric ceramic material as described in claim 1 or 2.
9. A method for preparing a piezoelectric ceramic element as described in claim 8, characterized in that, include: First, silver electrodes are prepared on the upper and lower surfaces of the PNN-PZT piezoelectric ceramic material prepared by the preparation method of any one of claims 3-7, and then the piezoelectric ceramic element is obtained by polarization treatment; wherein, the polarization treatment is polarization for 20 to 40 minutes at an electric field of 3 to 5 kV / mm at 25℃ to 60℃.
10. The application of the piezoelectric ceramic element as described in claim 8 in piezoelectric actuators, piezoelectric sensors, flexible macroscopic fiber composite material devices, ultrasonic transducers, active vibration control devices, precision positioning devices, and piezoelectric energy harvesting devices.